Addressing the Challenge of Counterfeits in Zimbabwe's Automotive Aftermarket Sector - Chitanha, Zebediah; Mujakachi, Tapiwa Christopher; Chiputura, Shelter; Kachilala, Tenson (International Journal of Supply Chain Management, 2026)
Counterfeit products are disrupting automotive supply chains globally, especially in the aftermarket sector. This study investigated and sought to address the challenge of counterfeits in the automotive aftermarket sector of Zimbabwe by applying the Extended Resource-Based Theory. This study employed the Interpretivism philosophy, the qualitative research approach, and a case study design. The researcher used interviews and a Focus Group Discussion (FGD) as research instruments. Purposive sampling was used to draw a sample of 23 participants that was made up of aftermarket businesspeople, automotive companies, a regional automotive association, policymakers, automotive clients, logisticians, researchers, and academia. The saturation point determined the cut-off point for the number of samples. Data analysis was carried out using Thematic Analysis. The study concluded that counterfeits are causing negative financial impacts on clients, automotive aftermarket businesses, and governments. Law enforcement enhancement, policy reviews, and stakeholder collaborations were identified as critical success factors in the fight against counterfeits in the automotive sector after-market. The major finding from the study was that application of the Extended Resource-Based Theory in the fight against counterfeits has the potential to mobilize strategic resources that can help bring back sanity to the local automotive aftermarket sector supply chains. The recommendations include conducting awareness campaigns that educate customers, training law enforcement agents in the requisite skills to combat counterfeits, and investing in technologies that detect and deter the smuggling and trading of counterfeits. Lastly, further research is recommended to establish the impact of policy on the fight against counterfeit automotive products and the role of technology in this fight. This paper contributes to policy and practice by advancing the application of the ERBT theory in driving collaborations to solve contemporary business challenges, such as counterfeiting in the automotive aftermarket sector supply chains.